Regional Note on Air Quality Management in the Western Balkans : Bosnia and Herzegovina, Kosovo, and North Macedonia - World Bank (World Bank, Washington, DC, 2020)
Ambient air pollution (AAP) is a serious global health problem that accounts for an estimated 4.2 million premature deaths worldwide per year. People in Eastern Europe and the Western Balkans are frequently exposed to air pollution levels above those considered safe, particularly in the winter. The increased exposure to air pollution and its linkage to higher prevalence of lung, respiratory, or chronic obstructive pulmonary disease (COPD) is also likely to increase the vulnerability of the affected population to the currently emerging COVID19 pandemic. In the Western Balkans, the residential sector is the largest source of harmful PM2.5 emissions. While not yet the dominant source of air pollution in the Western Balkans, transport-based emissions are gaining in prominence and in contrast to heating represent a year-round growing environmental challenge. The EU accession process provides an incentive to improve air quality in the Western Balkans by adapting legislation and learning from the experience of other EU countries. In addition to strengthening the legal and policy framework for air quality management (AQM) at the national level, it is important to develop subnational solutions, particularly for urban pollution hot spots. By acting on air pollution reduction, countries prepare the grounds for the long-term transition to a low-carbon economy and climate change mitigation, yet the synergies and trade-offs have to be carefully evaluated and understood.